Pengaruh Model Pembelajaran Kooperatif Tipe Think Talk Write Berbantuan Media Gambar Berseri terhadap Keterampilan Menulis Karangan Narasi Peserta Didik SD - Vani Sella Alfiana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jember, 2024)
Writing skills are the most complex language skills and are very important for students to master in the learning process. The phase B independent curriculum states that students are expected to be able to write an essay, one of which is a narrative essay. Innovation in using varied learning models is very necessary. The TTW type cooperative learning model is appropriate to use to overcome students' lack of ability in writing. The research was conducted at SDN Bangsalsari 03 Jember with the aim of finding out the influence of the TTW type cooperative learning model on the narrative essay writing skills of elementary school students. The type of research carried out was experimental research with a Posttest Only Control Group Design. The methods used are observation, interviews, performance tests, and documentation. The data analysis technique uses the independent sample t-test. The results of data analysis obtained a value of t count > t table (6.696 > 2.004), so it can be concluded that the TTW type cooperative learning model assisted by series of picture media has an effect on the narrative essay writing skills of class IV students at Bangsalsari 03 Jember Elementary School.
uploud by Tedyy_14.04.2026
Keywords: think talk write; series picture; writing skill; narrative essay